Effect of single spinal anesthesia with two doses ropivacaine on urinary retention after hemorrhoidectomy in male patients - Wang, Lei-lei; Kang, Meng; Duan, Li-xin; Chang, Xu-fei; Li, Xiao-xin; Guo, Xiang-yang; Kang, Zhi-yu; Han, Yong-zheng (Frontiers in Surgery, 2023)
Background: Anorectal diseases are common in the population and include internal, external, and mixed hemorrhoids. Although hemorrhoid surgery is a brief operation, anesthesia, anesthetic drugs, drug concentrations, and anesthesia level control are closely related to postoperative uroschesis. For hemorrhoid surgery, a single spinal block with ropivacaine is commonly used that blocks the S2-S4 parasympathetic nervous system, which in turn governs the voiding reflex, causing postoperative urinary retention; this affects the recovery of patients. This study was performed to investigate the effects of two doses ropivacaine that provided satisfactory analgesia and muscle relaxation and inhibited adverse reflexes on urinary retention after hemorrhoidectomy. Methods: The study included 200 male patients who underwent anorectal surgery with American Society of Anesthesiologists (ASA) grade I–II single elective spinal anesthesia between March 2021 and March 2022. Patients were randomly assigned to 2 groups using a random number table: Group A (n = 100) received 10 mg 0.5% ropivacaine (1.5 mL 1% ropivacaine + 1.5 mL 10% glucose = 3 mL), and Group B (n = 100) received 15 mg 0.5% ropivacaine (1.5 mL 1% ropivacaine + 1.5 mL 10% glucose = 3 mL). Results: The anal sphincter exhibited good relaxation, and no obvious traction pain or significant difference in the time of muscle strength recovery was observed between the 10 mg and 15 mg 0.5% ropivacaine groups (P > 0.05). The 10 mg 0.5% ropivacaine group had shorter time of micturition exceeding 100 mL and lower voiding International Prostate Symptom Score than the 15 mg 0.5% ropivacaine group (P < 0.01). Conclusions: Single spinal anesthesia with 10 mg 0.5% ropivacaine not only meets the needs for hemorrhoidectomy but also has less influence on postoperative uroschesis and is worthy of clinical application.